Application of extracellular vesicles in diabetic osteoporosis - Jia, Xiaopeng; Zhang, Gongzi; Yu, Deshui (Frontiers in Endocrinology, 2024)
As the population ages, the occurrence of osteoporosis is becoming more common.Diabetes mellitus is one of the factors in the development of osteoporosis. Compared with the general population, the incidence of osteoporosis is significantly higher in diabetic patients. Diabetic osteoporosis (DOP) is a metabolic bone disease characterized by abnormal bone tissue structure due to hyperglycemia and insulin resistance, reduced bone strength and increased risk of fractures. This is a complex mechanism that occurs at the cellular level due to factors such as blood vessels, inflammation, and hyperglycemia and insulin resistance. Although the application of some drugs in clinical practice can reduce the occurrence of DOP, the incidence of fractures caused by DOP is still very high. Extracellular vesicles (EVs) are a new communication mode between cells, which can transfer miRNAs and proteins from mother cells to target cells through membrane fusion, thereby regulating the function of target cells. In recent years, the role of EVs in the pathogenesis of DOP has been widely demonstrated. In this article, we first describe the changes in the bone microenvironment of osteoporosis. Second, we describe the pathogenesis of DOP.Finally, we summarize the research progress and challenges of EVs in DOP.